Air medical transportation in India: Our experience - Himanshu Khurana; Yatin Mehta; Sunil Dubey (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Long distance air travel for medical needs is on the increase worldwide. The condition of some patients necessitates specially modified aircraft, and monitoring and interventions during transport by trained medical personnel. This article presents our experience in domestic and international interhospital air medical transportation from January 2010 to January 2014. Material and Methods: Hospital records of all air medical transportation undertaken to the institute during the period were analyzed for demographics, primary etiology, and events during transport. Results: 586 patients, 453 (77.3%) males and 133 (22.6%) females of ages 46.7 ± 12.6 years and 53.4 ± 9.7 years were transported by us to the institute. It took 3030 flying hours with an average of 474 ± 72 min for each mission. The most common indication for transport was cardiovascular diseases in 210 (35.8%) and central nervous system disease in 120 (20.4%) cases. The overall complication rate was 5.3% There was no transport related mortality. Conclusion: Cardiac and central nervous system ailments are the most common indication for air medical transportation. These patients may need attention and interventions as any critical patient in the hospital but in a difficult environment lacking space and help. Air medical transport carries no more risk than ground transportation.